ANALISIS PENGARUH FAKTOR MIKRO TERHADAP TINGKAT RISIKO SAHAM DI BEI PADA TAHUN 2011-2013 Studi pada Perusahaan Penanaman Modal Asing di Bursa Efek Indonesia - Prattistia, Rensi Eka; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
Risk is an important factor that concerns investors because it will determine to which the investment objectives will be achieved. Risk is also the probability of achieving the required return investors. Based on the results of previous studies, the risk factors can be determined by both the micro and macro factors.The study population are the manufacturing sector listed on the Indonesian Stock Exchange in the year of 2011 - 2013 and its stock price data was obtained from Yahoo Finance. The analysis technique used is multiple regression, where Liquidity, DPR, DER, ROA, and ROE as independent variables and Stock’s Beta as the dependent variable.The results showed all the independent variables (Liquidity, DPR, ROA, ROE and DER) has no significant effect on stock risk (Beta).